Redukcjonizm, realizm naukowy i ontologia czasu i przestrzeni. Ontologia Zdzisława Augustynka - Gołosz, Jerzy (Filozofia Nauki, 2006)
The paper discusses the ontology of Zdzisław Augustynek, especially the part of this ontology that relates to space and time. This position is analyzed as an attempt to implement two methodological postulates, namely the postulates of reductionism and scientific realism.